LIFE NARRATIVE IN THE #RACEWARS: TERMINISTIC SCREENS AND TWITTER FIGHTS - Humphrey, Michael (AoIR Selected Papers of Internet Research, 2015)
Discourse on the Internet about race has created a new lens for observing what lies behind denial of white privilege, giving researchers a new opportunity to see how grand narratives become personal narratives. This paper examines examples of this phenomenon by looking at two denials of white privilege as they developed in digital spaces, and argues that the life stories we tell ourselves act as “terministic screens” (Burke, 1966), filters composed of language that distort common understanding. After examining the rhetoric of white privilege, I propose the development of “narratives of discomfort,” in which white people begin to re-tell their stories in the light of their privilege.